Paula Bruno, Alexandra Pita, Marina Alvarado, Embajadoras culturales. Mujeres latino-americanas y vida diplomática, 1860-1960, Rosario, Prohistoria, 2021, 168 pp - Rota, Alesson Ramon (2022)
Fil: Rota, Alesson Ramon. Universidad Di Tella; Argentina